(untitled) (Annals of Medical Research, 2021)
Aim: The changes in rat brain tissues treated with Crocin (Cr) as a protective agent in an acrylamide (AA) neurotoxicity model were investigated.Material and Methods: The present with of the experimental animal ethics committee at Inonu University, Faculty of Medicine (2016 / A-59). Forty male rats were randomly divided into 4 groups with study was conducted the approval equal number of rats (10): Control, Cr, AA, Cr + AA Groups. Malondialdehyde (MDA), reduced glutathione (GSH), total antioxidant status (TAS), total oxidant status (TOS), Oxidative stress index (OSI), superoxide dismutase (SOD), catalase (CAT) and protein values were examined in the brain tissues.Results: MDA, TOS and OSI levels increased in brain tissues of AA administered rats when compared to the other groups, while the GSH, TAS, SOD and CAT levels decreased in the group (p 0.05). GSH, TAS, SOD and CAT levels increased, but MDA, TOS and OSI levels decreased in the AA + Cr administered group when compared to the AA group (p 0.05). It was observed that oral AA administration altered the antioxidant/oxidant balance favoring the oxidants in male rat brain tissues, leading to oxidative stress induced neurotoxicity, while Cr administration reestablished the normal antioxidant/oxidant balance, preventing the oxidative stress induced neurotoxicity via detoxification. Conclusion: The present study concluded that the administered Cr dose was sufficient to prevent neurotoxicity and we recommend that adequate amounts of Cr should be consumed to prevent AA-induced toxicity and improve antioxidant capacity.